2016
DOI: 10.1371/journal.pone.0148425
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Effects of Developmental Exposure to Ethanol on Zebrafish Anxiety-Like Behaviour

Abstract: In zebrafish developmentally exposed to ambient ethanol (20mM-50mM) 1–9 days post fertilization (dpf), the cortisol response to stress has been shown to be significantly attenuated in larvae, juveniles and 6 month old adults. These data are somewhat at variance with similar studies in mammals, which often show heightened stress responses. To test whether these cortisol data correlate with behavioural changes in treated animals, anxiety-like behaviour of zebrafish larvae (9dpf and 10dpf) and juveniles (23dpf) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 60 publications
5
42
1
Order By: Relevance
“…The complexity is due to many factors. For example, the effect of alcohol exposure appears to be highly dose dependent with lower concentrations often not having any effect on anxiety responses in later life in humans (Jacobson et al., ) or in zebrafish (Baiamonte et al., vs. this study). The association between embryonic alcohol exposure and changes in anxiety later in life is also dependent upon the developmental stage at which the embryo was exposed to this substance (Zhang et al., ).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The complexity is due to many factors. For example, the effect of alcohol exposure appears to be highly dose dependent with lower concentrations often not having any effect on anxiety responses in later life in humans (Jacobson et al., ) or in zebrafish (Baiamonte et al., vs. this study). The association between embryonic alcohol exposure and changes in anxiety later in life is also dependent upon the developmental stage at which the embryo was exposed to this substance (Zhang et al., ).…”
Section: Discussionmentioning
confidence: 59%
“…These include, for example, erratic movement, vertical exploration of the tank, distance of the fish to bottom of the tank, and overall activity level (Gerlai, ; Maximino et al., ; Stewart et al., ). Previously, using a novel tank task after chronic embryonic alcohol exposure (8 days), Baiamonte and colleagues () found that embryonic alcohol exposure led to a decrease in anxiety‐related behaviors in adult zebrafish. It is not known, however, how an acute (2‐hour long) treatment with low concentrations of alcohol during embryonic development would affect anxiety in adult zebrafish.…”
mentioning
confidence: 99%
“…In summary, NPY-KO zebrafish exhibited less social behaviour under non-stressful conditions than wild-type fish, whereas under acute stress, they exhibited severe anxiety, similar to NPY-knockout mice and human psychiatric patients. Unlike previous studies of anxiety in zebrafish that used chemicals such as alcohol 47 , caffeine 48 and Y1 blockers 21 , anxiety behaviours were easily inducible and long-term observations were possible in NPY-KO zebrafish. These unique characteristics of NPY-KO zebrafish make them suitable experimental animals for studying psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Parker et al (2014) reported that zebrafish exposed to 0.12% ethanol for 7 days D r a f t spent significantly more time at the bottom of the tank compared to untreated controls. In contrast, adult fish exposed to 3% ethanol between 24 to 27 hpf were significantly higher in the water column compared to controls (Bailey et al 2015) suggesting an anxiolytic effect (Baiamonte et al 2016;Bailey et al 2015). Other groups have reported that exposure to 1% alcohol from 24 to 26 hours (hpf) had no effect on any measure of behavior of zebrafish to an animated predator (Seguin et al 2016).…”
Section: Behavior and Cognitionmentioning
confidence: 92%
“…Embryonic exposure to either 0.12% or 0.3% ethanol from 1 to 9 days postfertilization (dpf) led to a reduction in cortisol levels in response to a stressor, netting and exposure to air (Baiamonte et al 2015). Given that embryonic alcohol exposure led to a decrease in cortisol levels, these researchers measured several anxiety-related behaviors: (a) the time spent at the edge of the arena, thigmotaxis; (b) the time spent in the bright side of the arena, scototaxis and (c) novel tank diving (Baiamonte et al 2016). They found that compared to controls, alcohol-exposed fish spent less time in the periphery, more time at the top of the tank and less time in the dark side of the tank (Baiamonte et al 2016).…”
Section: Behavior and Cognitionmentioning
confidence: 99%